PCs all-in-one for dummies - Chambers, Mark L. (For Dummies, 2013)
A perfect companion for your desktop PC! Whether you use your PC for work or play, there's a lot to learn and a lot of territory to discover, so take along a good guide -- |c Source other than Library of Congress.